(3GdfcJ hGdaQhb deSGFd GdeOhfIs - (3CHh eMeO YHO GdMb Hf eMeO Hf gGQhf GdUbdjs; (3CHh YHO Gddg YHO GdQMef Hf GdbGSe GdeGdcj, CHh YHO Gddg,J (B191 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYRjR GdCcQe CeG HYO aEf HYV CUMGHfG SGdfi GdYfGjI HLejY eG jbY di , dCf GdeHJOF ai WdH Gdabg s
(3BNQgG (B:s
(3ajfXQ eG jaVd ef cSH hEf GSJhYH Pdc cd eG jHbi HjOg Je GdcJGH s
(3hQO GdYfhGf GdCUdi ai cX (B2 / 1644s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3HgG NQe s
Keywords: (3Gdabg GdeGdcjs